Berczeli Anzelm Károlyhoz - Lengyel Balázs (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1981)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek